FINANCIAL STATEMENT INTEGRITY IN THE CONSUMER NON CYCLICALS SECTOR: THE IMPACT OF FINANCIAL DISTRESS, EARNINGS MANAGEMENT, INSTITUTIONAL OWNERSHIP, AND BOARD INDEPENDENCE - Djenni Sasmita (ZILLZELL MEDIA PRIMA, 2025)
This study examines the determinants of financial statement integrity in Indonesian consumer non-cyclicals companies, focusing on the effects of financial distress, earnings management, institutional ownership, and independent commissioners. The research employs quantitative panel data regression analysis using secondary data from 32 companies listed on the Indonesia Stock Exchange during the 2019-2023 period, resulting in 160 firm-year observations. Data were analyzed using EViews 12.0 with Random Effects Model estimation based on hypothesis testing results. The results indicate that earnings management significantly reduces financial statement integrity, while independent commissioners significantly enhance it. Surprisingly, institutional ownership shows a significant negative relationship with financial statement integrity, suggesting potential short-termism among institutional investors. Financial distress demonstrates no significant effect on financial statement integrity, indicating companies maintain reporting quality despite financial challenges. The findings highlight the critical role of independent commissioners in ensuring financial reporting quality and suggest regulatory attention toward institutional investor behavior and earnings management practices. Companies should strengthen board independence and monitoring mechanisms to improve financial statement reliability. This research provides novel insights into the contradictory role of institutional ownership in emerging markets and demonstrates the resilience of financial reporting quality during financial distress in Indonesian consumer non-cyclicals companies, contributing to both agency theory and corporate governance literature in emerging market contexts.